Z problematyki rozwodów w Księstwie Warszawskim - Pomianowski, Piotr (Czasopismo Prawno-Historyczne, 2018)
This paper looks at civil divorce introduced in the Duchy of Warsaw by the provisions of the Napoleonic Code. It was initially believed that the number of civil divorces in the Duchy never exceeded ten and that the Napoleonic Code divorce regulations remained a dead letter of the law. However, a recent study of the remaining sources, including judicial fi les and marriage registers has shown that the scale of civil divorces was signifi cantly larger, with at least nearly a hundred cases recognised by civil tribunals of the Duchy of Warsaw between 1808 and 1812. Most of the divorce decrees were based on the Napoleonic Code although four were found to be issued based on the earlier Prussian Landrecht in force. The legal grounds on which a civil divorce was most frequently adjudicated were the provisions of article 231 (exces, sevices ou injures graves) and article 230 (infi delity). Most petitioners for a divorce were women and 80% of their petitions were successful. Women would also be given custody of the minors and child maintenance. Civil divorce was sought by representatives from the whole spectrum of society (gentry, craftsmen, tradesmen, workers). Regarding religious affi liation of the petitioners, Catholics constituted the largest group.